Assessing the Quality of Life Among Commuting Workers and Uncomfortable Travel (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Many studies conclude commuting that has an impact on the quality of life of the commuter both in the physical, psychological, health, and environmental aspects of the commuter. Increased risk of musculoskeletal disorder (MSD), obesity, increased blood pressure, and low physical health conditions are found in prolonged commuting activities as the existing problem in public health. This study using cross sectional design with WHO QOL BREF questionnaire.Â  The total sample 155 respondents of commuting working using KRL Commuter Line Bogor to Jakarta in 2018. The initial model for assessing the relationship directly and indirectly between quality of life among commuting workers and travel uncomfortable, health complaint, psychological condition, bad experience, and income was constructed on the basis of severe hypotheses Based on the results of the path analysis it was found that income has a direct effect on quality of life. Psychological conditions have a direct effect on quality of life. Psychological condition is intervening variable for travel uncomfortable and health complaints as indirect effect. These results may help to identify the direct factor to improve the quality of life among commuting workers and as a basis for developing policies to improve the quality of public transportation services for commuting workers, and as a basis for formulating policies related to housing development locations that are integrated with public transportation facilities.